2019
DOI: 10.1186/s41938-019-0163-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential of entomopathogenic nematode isolates from Rwanda to control the tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae)

Abstract: Tomato leaf miner, Tuta absoluta (Meyrick), is a major threat to tomato production as it can cause up to 100% yield loss under both greenhouse and open-field conditions. Chemical control, which is associated with several undesirable effects, remains the only option readily available for this pest since its invasion of Rwanda in the year 2015. This study assessed the potential of using local isolates of entomopathogenic nematodes (EPNs) in management of T. absoluta in Rwanda. Six EPNs including four locally iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…The ability of EPNs to reach and kill T. absoluta larvae in leaf galleries was also reported (Batalla-Carrera et al, 2010;Van Damme et al, 2016;Kamali et al, 2018). The local EPN isolates were able to kill T. absoluta and had even been found to be effective against white grubs in Rwanda (Kajuga et al, 2018;Ndereyimana et al, 2019), while it was not easy to nd EPNs which can kill them (Laznik et al, 2015). Although EPNs live naturally in soil, different researchers found that they can be used on above-ground parts of the plant to control effectively the pests living in cryptic habitats like in leaf galleries (Batalla-Carrera et al, 2010;Garcia-del-Pino et al, 2013;Lankin et al, 2021), which concurs with the results of the present study under laboratory conditions.…”
Section: Discussionmentioning
confidence: 79%
“…The ability of EPNs to reach and kill T. absoluta larvae in leaf galleries was also reported (Batalla-Carrera et al, 2010;Van Damme et al, 2016;Kamali et al, 2018). The local EPN isolates were able to kill T. absoluta and had even been found to be effective against white grubs in Rwanda (Kajuga et al, 2018;Ndereyimana et al, 2019), while it was not easy to nd EPNs which can kill them (Laznik et al, 2015). Although EPNs live naturally in soil, different researchers found that they can be used on above-ground parts of the plant to control effectively the pests living in cryptic habitats like in leaf galleries (Batalla-Carrera et al, 2010;Garcia-del-Pino et al, 2013;Lankin et al, 2021), which concurs with the results of the present study under laboratory conditions.…”
Section: Discussionmentioning
confidence: 79%
“…The ability of EPNs to reach and kill T. absoluta larvae in leaf galleries was also reported (Batalla-Carrera et al, 2010;Van Damme et al, 2016;Kamali et al, 2018). The local EPN isolates were able to kill T. absoluta and had even been found to be effective against white grubs in Rwanda (Kajuga et al, 2018;Ndereyimana et al, 2019), while it was not easy to nd EPNs which can kill them (Laznik et al, 2015). Although EPNs live naturally in soil, different researchers found that they can be used on above-ground parts of the plant to control effectively the pests living in cryptic habitats like in leaf galleries (Batalla-Carrera et al, 2010;Garcia-del-Pino et al, 2013;Lankin et al, 2021), which concurs with the results of the present study under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…More than 100 species of EPNs have been identi ed worldwide (about 80% by steinernematid) and at least 13 of these species have been marketed (Shapiro-Ilan et al, 2014;Ndereyimana et al, 2019). In general, the natural violence against various insect species varies between EPN species.…”
Section: Introductionmentioning
confidence: 99%
“…This is crucial in the fight against impending food crisis, combating hunger and promoting food security in the continent. For instance, the biocontrol efficacy of a native EPN species was demonstrated against the devastating tomato leaf miner, Tuta absoluta Meyrick Lepidoptera: Gelechiidae, which was reported as a serious pest against tomato production in many African countries (Ndereyimana et al, 2019;Dlamini et al, 2020). It is therefore important to identify species that are adaptable to existing IPM systems, well suited to native environmental conditions, and which could be mass-produced for industrial and commercial purposes.…”
Section: Introductionmentioning
confidence: 99%